(untitled) (The Agriculturists, 2018)
This study was conducted at the Horticultural Farm of Sher-e-Bangla Agricultural University, Dhaka during October, 2015 to January, 2016 to determine the effects of mulches and phosphorus on the growth and yield of squash (Cucurbita pepo). The experiment consisted of two factors. Factor A: different mulches and Factor B: phosphorus (3 levels). The experiment was laid out in a Randomized Complete Block Design with three replications. Mulches and phosphorus showed significant effects on most of the parameters. In case of mulches, highest individual fruit weight (328.0 g) and fruit yield (37.0 tha-1) was recorded from black polythene, whereas the lowest fruit weight (280.8 g) and fruit yield (21.5 tha-1) was recorded from control. In case of phosphorus, highest individual fruit weight (300.4 g) and fruit yield (31.3 tha-1) was recorded from 90 kg P2O5/ha,whereas the lowest fruit weight (290.4 g) and fruit yield (26.2 tha-1) was recorded from control. For combination, highest individual fruit weight (338.2 g) and fruit yield (39.9 t ha-1) were recorded from black polythene with 90 kg P2O5/ha while the lowest individual fruit weight (272.2 g) and fruit yield (19.7 t ha-1) were recorded from control treatment. Black polythene mulch with 90 kg P2O5/ha was found suitable for squash cultivation under the condition of the study. The Agriculturists 2018; 16(2) 25-34